2013
DOI: 10.1590/s2237-93632013000100005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for prolonged length of stay after colorectal surgery

Abstract: Morbidity Length of stay a b s t r a c tObjective: Colorectal surgeons often struggle to explain to administrators/payers reasons for prolonged length of stay (LOS). This study aim was to identify factors associated with increased LOS after colorectal surgery. Design:The study population included patients from the 2007 American-College-of-Surgeons-National-Surgical-Quality-Improvement-Program (ACS-NSQIP) database undergoing ileocolic resection, segmental colectomy, or anterior resection. The study population w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…We found no significant impact of stoma type on prolonging LOS; however, having stoma formation compared to not having stoma formation increases the odds of extending LOS to about 2.5 times. As seen in other published studies, our study also confirms the significance of hypertension, Eastern Cooperative Oncology Group (ECOG) performance, the American Society of Anesthesiologists (ASA) grading assessment, and grade of differentiation on LOS after colorectal surgery (31)(32)(33). Among the demographic features in this study, sex was the only one that significantly influenced prolonged LOS, and this was well described in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…We found no significant impact of stoma type on prolonging LOS; however, having stoma formation compared to not having stoma formation increases the odds of extending LOS to about 2.5 times. As seen in other published studies, our study also confirms the significance of hypertension, Eastern Cooperative Oncology Group (ECOG) performance, the American Society of Anesthesiologists (ASA) grading assessment, and grade of differentiation on LOS after colorectal surgery (31)(32)(33). Among the demographic features in this study, sex was the only one that significantly influenced prolonged LOS, and this was well described in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The LOS for English patients also appears to compare relatively favorably to equivalent international figures. [8,10,25] …”
Section: Discussionmentioning
confidence: 99%
“…Chiu et al state that minor and major complications were better predictors of LOS than preoperative demographic and disease parameters [ 46 ]. Sex, congestive heart failure, weight loss, Crohn’s disease, preoperative albumin < 3.5 g/dL and hematocrit < 47%, baseline sepsis, ASA class ≥ 3, open surgery, surgical time ≥ 190 min, post-operative pneumonia, failure to wean from mechanical ventilation, deep venous thrombosis, urinary tract infection, systemic sepsis, surgical site infection and reoperation within 30-days from the primary surgery were the risk factors for prolonged LOS [ 47 ]. In contrast, this study found age, ASA grade, operative time, presence or absence of a stoma, robotic or laparoscopic approach to surgery, and complications are the significant predictor variables of LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has used a limited number of variables to investigate LOS, mortality and readmission following CRC surgery [7,8,10,19,[39][40][41][42]. This study includes a larger number of variables (47) including demographics, peri-and post-operative outcomes, surgical approaches, complications and mortality. These variables are used and compared in predicting LOS, mortality and readmission.…”
Section: Role Of Data Analytics and Machine Learningmentioning
confidence: 99%